Cultural adaptation of web design services as critical success factor for business excellence: A cross-cultural study of Portuguese, Brazilian, Angolan and Macanese web sites. Issue 2 (29th April 2014) - Calabrese, Armando; Capece, Guendalina; Di Pillo, Francesca; Martino, Federico
Abstract : Purpose: – The purpose of this paper is to examine whether cultural backgrounds of nations are expressed through the web design of their companies. Actually, it investigates whether, in countries characterized by the same cultural matrix and language but by different national backgrounds, the cultural specificities of a country are a critical success factor for web design and enablers of business excellence. Design/methodology/approach: – Starting from a deep literature review, four research hypotheses on the relationship between cultural background and web design are formulated. By employing both the content analysis and the cross-tabulation methodology, these hypotheses are tested. Findings: – Brazilian, Portuguese, Angolan and Macanese web sites show that companies operating in these countries are aware that cultural background is a necessary success factor to consider for improving cross-cultural management of computer-mediated communication. Indeed, the findings confirm that the internet is not a culturally neutral communication medium. By providing evidences of web site cultural adaptation, this study supports the use of a targeted approach to web site design and provides managerial guidelines for improving business excellence of companies' online environment. Originality/value: – The paper offers insights into the topic of a culturally adapted computer-mediated communication for improving consumer experience.